2005
DOI: 10.1177/0306624x04273433
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Validation of the Self-Appraisal Questionnaire: A Tool for Assessing Violent and Nonviolent Recidivism With Female Offenders

Abstract: The Self-Appraisal Questionnaire (SAQ) is a 72-item self-report measure designed to predict violent and nonviolent recidivism among adult male criminal offenders. It was administered to 91 female offenders incarcerated in Pennsylvania and 183 incarcerated in Singapore correctional systems. Results indicated that the SAQ has sound psychometric properties, with acceptable reliability and concurrent and predictive validity for assessing violent and nonviolent recidivism. There were no significant differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 31 publications
4
35
0
Order By: Relevance
“…The Self-Appraisal Questionnaire (SAQ; Loza, 1996) The SAQ consists of 72 'true' or 'false' items and has seven clinical subscales and a validity subscale. The clinical subscales are: Criminal Te ndencies (antisocial attitudes, beliefs, behaviours, and feelings), Antisocial Personality Problems (characteristics similar to those used to diagnose antisocial personality disorder), Conduct Problems (assesses childhood behavioural problems), Criminal History, Alcohol/Drug Abuse, Anti-Social Associates (the offender's perception of the effect of his associates on his criminal activities), Anger (measures reaction to anger).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Self-Appraisal Questionnaire (SAQ; Loza, 1996) The SAQ consists of 72 'true' or 'false' items and has seven clinical subscales and a validity subscale. The clinical subscales are: Criminal Te ndencies (antisocial attitudes, beliefs, behaviours, and feelings), Antisocial Personality Problems (characteristics similar to those used to diagnose antisocial personality disorder), Conduct Problems (assesses childhood behavioural problems), Criminal History, Alcohol/Drug Abuse, Anti-Social Associates (the offender's perception of the effect of his associates on his criminal activities), Anger (measures reaction to anger).…”
Section: Methodsmentioning
confidence: 99%
“…Further, self-reported antisocial personality characteristics, such as those reported by Blackburn and Fawcette (1995) have been shown to predict violent recidivism (Quinsey et al, 1998) and Kuriychuk (1990) found concordance between Blackburn's self-reported scales and the PCL-R. Self-reported psychopathology has also been shown to be predictive of institutional adjustment problems in samples of both violent and sexual offenders (Mills and Kroner, 2003a). In addition, the Self Appraisal Questionnaire (SAQ: Loza, 1996), a self-report questionnaire which was designed specifically to predict offender general and violent recidivism, was repeatedly found to be reliable and valid and at least as effective in predicting offender post-release outcome when compared with four other widely used and professional rated measures (Loza et al, 2000;Kroner and Loza, 2001;Loza and Loza-Fanous, 2001). Paulhus (1984) holds to a two-dimensional nature of social desirability: impression management and self-deception.…”
Section: Introductionmentioning
confidence: 98%
“…On the one hand, the low internal consistency of these subscales could be attributable to the small number of items on them. On the other hand, Kubiak et al (2014), Loza, Neo, Shahinfar, and Loza-Fanous (2005), and Mitchell, Caudy, and MacKenzie (2013) found similar issues and pointed to small sample sizes and low inter-item correlations as possible explanations for low internal consistency. That the findings of the present research replicate these problems may point to the need for further developmental work on the SAQ subscales.…”
Section: Discussionmentioning
confidence: 94%
“…In keeping with Webster and colleagues' ( 1997 ) original intentions, these factors should be considered when planning interventions to manage risk, and not necessarily as a predictor of violence or reoffending. Loza, Neo, Shahinfar, and Loza-Fanous ( 2005 ). Loza et al ( 2005 ) compared the scores of 91 female offenders incarcerated in Pennsylvania to the scores of 183 female offenders incarcerated in a Singapore correctional system on the SelfAppraisal Questionnaire (SAQ; a 72-item selfreport measure designed to predict violent and nonviolent recidivism among adult male criminal offenders).…”
Section: Research Specifi C To Risk Assessment With Asian Populationsmentioning
confidence: 99%